Utilization of ladle slag for soil stabilization - Xu, Bo (Nanyang Technological University, 2021)
Global sustainable development faces challenges in greenhouse gas emission, consumption of nonrenewable resource and energy, waste dumping/landfilling, and environmental pollution. In this context, this study focuses on two sustainable development problems. Firstly, in geotechnical engineering, ordinary Portland cement (OPC) is widely used for the stabilization of problematic soils, including soft clay and contaminated soil, but the production of OPC consumes significant nonrenewable resources and energy, and generates CO2. Secondly, a large amount of ladle slag (LS) containing heavy metals, a by-product of steel industry, is generated worldwide every year and is dumped in landfills, causing both environmental and economic issues. Hence, this study aims to reuse LS to replace OPC for soil stabilization to achieve sustainable development goals, including CO2 emission reduction, consumption of nonrenewable resources and energy reduction, LS dumping/landfilling reduction, strength enhancement, and heavy metal immobilization. There are two different approaches introduced in this study, including using LS-activated ground granulated blastfurnace slag (GGBS), a by-product generated during iron making, for soft clay stabilization, and using LS-CO2 for stabilization/solidification (S/S) of contaminated soil. In the first part of this study (Chapters 3 to 5), LS-GGBS blend was used as the binder for soft clay stabilization. The results showed that the LS-GGBS-stabilized clay with LS:GGBS ratio of 2:8~5:5 could achieve similar or higher unconfined compressive strength (UCS) compared with OPC-stabilized clay after curing for 56 days. However, the 28-day strength, which is usually used for design, of LS-GGBS-stabilized clay was lower than that of OPC-stabilized clay. Hence, the phosphogypsum (PG), a by-product from manufacturing fertilizer, was used to enhance the strength development of LS-GGBS-stabilized soft clay. With PG:(LS+GGBS) ratios of 10~20%, the LS-GGBS-PG-stabilized clay could achieve higher 28-day strength than that of OPC-stabilized clay. The leaching of heavy metals from the LS-GGBS-PG-stabilized clay could satisfy the requirements of inert waste and three common drinking water regulations. Therefore, using LS-GGBS-PG blend to replace OPC for soil stabilization is a feasible solution, which can also reduce CO2 emission, consumption of nonrenewable resources and energy, LS dumping/landfilling, and cost of binders. In the second part of this study (Chapters 6 and 7), the use of LS-CO2 for the immobilization of heavy metals from both internal and external sources was investigated. The results showed that LS had carbonation reactivity and could sequester CO2. The carbonation effectively reduced the leaching of heavy metals from LS (i.e., internal source), especially for Pb and Zn. The strength of carbonated LS was two orders of magnitude higher than that of uncarbonated LS. Then, LS and CO2 were used for the S/S of lead (Pb)-contaminated soil (i.e., external source). The results showed that LS-stabilized Pb-contaminated soil could sequester CO2 up to 18% of LS mass. After carbonation, the concentration of leached Pb from LS-stabilized contaminated soils with Pb concentrations of 2000~6000 mg/kg were significantly reduced, satisfying the limits of inter waste and three drinking water regulations. The LS-stabilized Pb-contaminated soil yielded more than three times higher UCS than that of uncarbonated soils. This method can also sequester CO2, reduce the consumption of nonrenewable resources and energy, LS dumping/landfilling, and cost of binders.